Menejemen Sarana Prasarana dalam Meningkatkan Mutu Lulusan di Mts Negeri Triwarno Kutowinangun Kebumen - Ahmad Safingudin (LPPM IAINU Kebumen, 2020)
Infrastructure is an important factor in improving the quality of graduates, the Triwarno Kutowinangun Kebumen State Madrasah Tsanawiyah in the last two years has been very concerned about the fulfillment of facilities and infrastructure, this study aims to: (1) Review and discuss the Management Planning of Educational Facilities and Infrastructure in Improving the Quality of Graduates in MTs Negeri Triwarno Kutowinangun Kebumen, (2) Analyzing the Organization of Educational Facilities and Infrastructure Management in Improving the Quality of Graduates in MTs Negeri Triwarno Kutowinangun Kebumen. (3). Analyzing and Discussing Instructions for the Management of Educational Facilities and Infrastructure in Improving the Quality of Graduates at MTs Negeri Triwarno Kutowinangun Kebumen. (4). Analyzing Management Control of Educational Facilities and Infrastructure in Improving Graduate Quality at MTs Negeri Triwarno Kutowinangun Kebumen.This study uses a qualitative method. The research was conducted at MTs Negeri Triwarno Kutowinangun Kebumen, from May to October 2017. The subjects in this study were the Head of Madrasah and Deputy Head of Facilities and Infrastructure of MTs Negeri Triwarno Kutowinangun Kebumen. The informants in the study were teachers and students. Data collection techniques by means of interviews, observation and documentation. The data validation technique uses data triangulation and source triangulation. Data analysis techniques using interactive methods, data collection, data presentation, data reduction and drawing conclusions.The results of the study revealed that the management of facilities and infrastructure in improving the quality of graduates at MTs Negeri Triwarno Kutowinangun Kebumen was carried out by (1) Planning for Facilities and Infrastructure (Planing), namely madrasah coordination meetings, determining the madrasah program, and determining the need for educational facilities and infrastructure. (2) Organizing of Facilities and Infrastructure (Organizing) includes setting up the organizational structure of managing facilities and infrastructure, dividing work assignments/job descriptions, arranging practice tools and materials, and setting practical activities. (3) Directing of Facilities and Infrastructure (Actuating) in the form of procurement, maintenance and elimination of facilities and infrastructure. (4) Facility and Infrastructure Control (Controling) is carried out by taking an inventory. The use of facilities and infrastructure should be adjusted to the needs in order to obtain benefits from such use. All madrasah residents should take advantage of the facilities and infrastructure owned by the madrasa so that they are not wasted just being a decoration because basically all madrasa facilities are held to provide the best service to all madrasa residents. Maintenance of madrasa facilities and infrastructure is not only left to the officers who handle them, but the contribution or proactiveness of all madrasa residents is also needed so that all programs planned for maintaining madrasas can be realized properly for the continuity of the education process in madrasas. Keywords: Management, Infrastructure, Quality of Graduates